Website-based Scientific Traditional Medicine Information Prototype - Nurul Umi Salamah; Nur Reviana Majid; Ahmad Faiz Makarim; Prasojo Pribadi; Setiyo Budi Santoso (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The article presents a website-based design for traditional medicine information that can be traced to its truth value based on scientific literature. The author arranges the application workflow using draw.io online diagram software. Preparation of interface design recommendations using the Microsoft Power Point application. The flow of the process of searching for traditional medicine information data begins when the user presses the start button, then the main menu will appear, then search or view data on various traditional medicines. traditional medicines, benefits, method of use and dosage.